Effect of a three-dimensional hyperbranched structure on the ionic conduction of metallo-supramolecular polymers. Issue 61 (4th July 2015) - Pandey, Rakesh K.; Hossain, Md. Delwar; Sato, Takashi; Rana, Utpal; Moriyama, Satoshi; Higuchi, Masayoshi
<x xml:space="preserve">Abstract</x> 3D metallo-supramolecular polymers exhibited 10–100 times higher ionic conductivity than their 1D equivalents due to the improved ion conduction pathway.